2018
DOI: 10.1186/s13643-018-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for successful trauma registry implementation in low- and middle-income countries—protocol for a systematic review

Abstract: BackgroundThe benefits of trauma registries have been well described. The crucial data they provide may guide injury prevention strategies, inform resource allocation, and support advocacy and policy. This has been shown to reduce trauma-related mortality in various settings. Trauma remains a leading cause of mortality in low- and middle-income countries (LMICs). However, the implementation of trauma registries in LMICs can be challenging due to lack of funding, specialized personnel, and infrastructure. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This helps, as shown; to reduce the number of fatalities occurring due to traumatic incidents. 26 It has been confirmed that by establishing trauma registries, a number of developments have occurred in health care systems and the process of policy-making in the health systems of developing countries. 27 One of the essential pre-requisites to establishing a trauma center is to use an integrated and simultaneous trauma registry as a standard information collection system to enhance system performance.…”
Section: Discussionmentioning
confidence: 98%
“…This helps, as shown; to reduce the number of fatalities occurring due to traumatic incidents. 26 It has been confirmed that by establishing trauma registries, a number of developments have occurred in health care systems and the process of policy-making in the health systems of developing countries. 27 One of the essential pre-requisites to establishing a trauma center is to use an integrated and simultaneous trauma registry as a standard information collection system to enhance system performance.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have highlighted this need particularly in low- and middle-income countries where the impact of consequences of injuries is disproportionately high [ [11] , 12. , [13] , [14] , [15] , [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
“…What factors are associated with knee extension angle or loss of extension? Summary and descriptive statistics will be reported in terms of means, standard deviations, medians and ranges, as appropriate [25].…”
Section: Methods and Analysismentioning
confidence: 99%